영아 및 어머니의 기질과 부모효능감과의 관계 - 윤혜정(Hye Jung Yun); 현온강(On Kang Hyun) (Korean Journal of child studies, 2007)
The subjects, 114 mothers with infants from 6- to 24- months of age, were administered the Infant Behavior Questionnaire-Revised(Gartstein & Rothbart, 2003), Adult Temperament Questionnaire (Derryberry & Rothbart, 1988) and Parenting Efficacy(Park & Rha, 2003; Lederman, Weigarten & Lederman, 1981) Boys were more distressed than girls in limitation and in falling reactivity/rate of recovery. Parenting efficacy was greater for mothers with daughters than mothers with sons. Infants' fear and distress to limitation correlated positively with mothers' sadness. Infants' attention span correlated positively with mothers' attentional control, inhibition control and positive control. Parenting efficacy was higher in mothers whose children fall asleep easily and have longer attention spans. Mothers' positive affect and activation control increased and frustration decreased parenting efficacy. KCI Citation Count: 11